Phylogenomics, evolution of trophic traits and divergence times of hemiodontid fishes (Ostariophysi: Characiformes) - Nogueira, Acácio Freitas [UNESP]; Oliveira, Claudio [UNESP]; Langeani, Francisco [UNESP]; Netto-Ferreira, André L. (Elsevier, 2023)
The South American characiform family Hemiodontidae comprises five genera and 34 species. The family lacks comprehensive phylogenetic hypotheses resolving its species relationships. The studies that addressed these questions exhibited a narrow taxon sampling or used single-locus markers. Herein we surveyed hundreds of ultraconserved elements (UCEs) loci to provide the first molecular phylogenetic hypothesis and divergence time estimates for hemiodontids encompassing all its genera and most species (27 of the 34 valid species). We also tracked the history of the protractile upper jaw in the genera Argonectes and Bivibranchia across the recovered phylogenies through ancestral state reconstruction. Our results corroborate the monophyly of Hemiodontidae and the genera Argonectes and Bivibranchia in all phylogenetic methods with maximum clade support. The genera Anodus and Hemiodus were not monophyletic because Anodus elongatus was sister to the monotypic Micromischodus instead of A. orinocensis, and H. immaculatus did not form a clade with its other congeners, but instead was sister to the clade including Anodus and Micromischodus. All remaining species of Hemiodus were placed together into a monophyletic group, where they were arranged into four major subclades. The relationship in the family is summarised as: (Bivibranchia, (Argonectes, ((H. immaculatus, (Anodus, Micromischodus)), Hemiodus clade))), in discordance with the morphological phylogeny that placed all genera monophyletic and resolved the family as: ((Anodus, Micromischodus), (Hemiodus, (Argonectes, Bivibranchia))). The origin of Hemiodontidae was estimated from the Late Cretaceous to the Middle Paleogene, with the mean age in the Paleocene, while the origin of most hemiodontid genera except Bivibranchia occurred in the Miocene. Unordered parsimony and likelihood reconstruction indicates that Argonectes and Bivibranchia developed their protractile upper jaw independently.
Keywords: Halftooths; Hemiodontidae; Neotropical fishes; Phylogeny; South America; Ultraconserved elements